Pluralisme Berbasis Tauhid di Indonesia: Studi Analisis Terhadap Pemikiran Nurcholish Madjid - Feryani Umi Rosidah; Ali Mursyid Azisi; Kunawi Basyir (NALAR, 2023)
This article specifically analyzes monotheism-based pluralism in Indonesia from the perspective of Nurcholish Madjid. Often, in reality, religion does not exist as a unifying tool for its people, but instead creates divisions. Both the internal and external divisions of the ummah due to the differences they have caused, for example the burning of places of worship, injuries, loss of life, both material and immaterial losses, etc. Monotheistic-based pluralism is relevant in Indonesia, especially in promoting tolerance, peace and understanding between religions. Regarding pluralism, it is not enough if their understanding is limited to the discourses that are on the air. The implementation of attitudes and behavior lies in the adherents of each community (religion), who have been given an understanding by each of the religious leaders they adhere to. The research method in this article uses descriptive qualitative analysis, and data collection uses library research steps. The primary source of data is taken from Nurcholish Madjid's thoughts in the form of his book, and the primary source comes from scientific journals that are relevant to this study. In the results of this study, that Tawhid is interpreted as the Oneness of God which has implications for accepting awareness of human equality and dignity in their position as God's creatures. Humans look only to God, and to fellow human beings as a series of equals. That is, the divine principle will give birth to an understanding of human equality. In other words, the concept promoted by Nurcholish Madjid is that all humans in terms of basic dignity and worth are the same. None of our fellow human beings has the right to undermine or dominate the dignity and value of another human being. According to him, differences are God's provisions which have implications for the teachings of monotheism itself. This article adds to the body of knowledge, especially in the study of pluralism and the field of study of religions.Keywords :Pluralism;Tauhid; Nurcholish Madjid;Indonesia